Innovations in Blade Design for Enhancing Wind Turbine Efficiency: A Review of Aerodynamic, Structural, and Material Advancements - Parankush Koul (International Journal of Energetica, 2025)
This paper reviews the most significant aerodynamic, structural, and material advances in wind turbine blades. If the market is to be more sustainable, wind turbine efficiency becomes an important consideration. The article highlights the aerodynamic innovations that refine blades to optimize performance and capture more energy in higher lift-to-drag ratios. The structural advancement is based on high-end design techniques for high performance in extreme conditions to eliminate maintenance costs. Then there are the material improvements, such as lightweight, robust composites that make for longer blades with the ability to capture more energy without compromising strength. This multidimensional approach is, overall, crucial to widespread utilization of wind as a sustainable and affordable energy source against the backdrop of increasing energy needs.